(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To determine the prevalence of incontinence-associated dermatitis (IAD) and factors associated with its occurrence in adult patients admitted to intensive care units (ICUs). Method: This is an observational, epidemiological, cross-sectional, point-prevalence study conducted in ICUs with a sample of 40 patients. The following statistical tests were applied: Fisher’s exact test, Student’s t-test, Mann-Whitney test, and logistic regression. Results: The prevalence of IAD was found to be 22.5%. After univariate and bivariate analysis of associated factors, logistic regression was performed on variables with a p-value less than 0.20. Only the variable “sedated patient” was found to be statistically significant, which means that a sedated patient is 5.4-fold more likely to develop IAD compared to the population without IAD. Conclusion: The prevalence of IAD found in this study may assist in the planning of healthcare resources, interventions, and prevention strategies, as well as help institutions compare IAD indicators in similar populations. In addition, the finding that sedated ICU patients were 5.4-fold more likely to develop IAD may be useful in developing targeted prevention strategies for this population. DESCRIPTORS: Prevalence. Intensive care units. Enterostomal therapy. Diaper rash.